2006
DOI: 10.1212/01.wnl.0000198208.59347.96
|View full text |Cite
|
Sign up to set email alerts
|

MRI evidence of mesial temporal sclerosis in sporadic “benign” temporal lobe epilepsy

Abstract: MRI-detected mesial temporal sclerosis is often encountered in patients with sporadic benign temporal lobe epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
73
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 41 publications
(14 reference statements)
11
73
0
1
Order By: Relevance
“…Structural neuroimaging is recommended for all children with recently diagnosed localization-related or generalized epilepsy who do not have the clinical and electrographic features characteristic of classical idiopathic focal or generalized epilepsy (these include benign epilepsy with centrotemporal spikes, childhood absence epilepsy, juvenile absence epilepsy, and juvenile myoclonic epilepsy) 16,[31][32][33] . However, this series shows how structural abnormalities judged to be etiologically related to the seizure conditions have been found in idiopathic focal or generalized epilepsy, which are consistent with other published data 23,34,35 . This possibility suggests that clinicians should consider obtaining structural neuroimaging with an MRI when feasible for all patients with epilepsy, because MRI abnormalities may be present even in children with apparently benign syndromes or cryptogenic seizures, and the discovery of an epileptogenic lesion has potential implications for diagnosis, prognosis and treatment.…”
Section: Whole Samplesupporting
confidence: 92%
“…Structural neuroimaging is recommended for all children with recently diagnosed localization-related or generalized epilepsy who do not have the clinical and electrographic features characteristic of classical idiopathic focal or generalized epilepsy (these include benign epilepsy with centrotemporal spikes, childhood absence epilepsy, juvenile absence epilepsy, and juvenile myoclonic epilepsy) 16,[31][32][33] . However, this series shows how structural abnormalities judged to be etiologically related to the seizure conditions have been found in idiopathic focal or generalized epilepsy, which are consistent with other published data 23,34,35 . This possibility suggests that clinicians should consider obtaining structural neuroimaging with an MRI when feasible for all patients with epilepsy, because MRI abnormalities may be present even in children with apparently benign syndromes or cryptogenic seizures, and the discovery of an epileptogenic lesion has potential implications for diagnosis, prognosis and treatment.…”
Section: Whole Samplesupporting
confidence: 92%
“…1 Our group provides strong evidence about the existence of a common, often unrecognized clinical entity called benign TLE, which is characterized by seizure onset in adulthood, frequent familial history, rare simple partial seizures, and radiologic evidence of hippocampal sclerosis (Hs) in almost 40%, which was previously considered synonymous with drug-resistant epilepsy. 2,3 Moreover, using voxel-based morphometry and cortical thickness we have confirmed mesial temporal lobe, parietal lobe, and thalamic abnormalities that were remarkably comparable to what is observed in patients with refractory TLE regardless of the presence of Hs. 4,5 Of interest, our observations in benign TLE are consistent with the brain regions reported by Keller et al 1 This finding further enlarges the thalamocortical network being observed, even in patients with very mild epilepsy.…”
supporting
confidence: 77%
“…[1][2][3] More recently, we have shown that MR imaging evidence of Hs is present in a third of patients with drug-responsive TLE, a finding that indicates that Hs itself does not necessarily mean intractable epilepsy. 3 In daily clinical practice, it has become increasingly clear that MR imaging signs of Hs must always be carefully interpreted because they may occur as incidental findings in patients without epilepsy. 4 Most important, we recently found, in approximately 25% of healthy controls, either unilateral or bilateral Hh, whereas hippocampal atrophy, whether or not associated with hyperintensity, was seen exclusively in patients with TLE.…”
mentioning
confidence: 99%